The Implementation Of Flipped Classroom In Enhancing Self-Regulated Learning And Efl Speaking Competence In A Higher Learning Institution In China - Zhong, Linling (2023)
Self-regulated learning and EFL speaking competence are considered to be important skills that students need to master in the 21st century. Especially in the rapid development of China's economy, Chinese students need to have self-regulated learning and EFL speaking competence, especially speaking fluency, to meet the current requirements issued by the Ministry of Education of China. However, Chinese EFL students have consistently performed poorly in self-regulated learning and speaking. Therefore, this study intends to investigate the implementation of flipped classroom in enhancing students’ self-regulated learning and EFL speaking competence in the context of China and probes into the dynamic learning process from the perspective of students’ own experiences, viewpoints, cognition, and emotion, to provide personal and lived insights into the process of students' demonstration of self-regulated learning and speaking learning in the flipped classroom.